1972
DOI: 10.1192/bjp.120.554.41
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Extra-pyramidal Disorders and Psychiatric Relapse after Withdrawal of Long-Term Phenothiazine Therapy

Abstract: It has been said that any drug which is active and produces an effect which is beneficial must also, under similar or different circumstances, have side-effects which are neither beneficial nor desired (Hamilton, 1965). It is the balance between desired and undesired actions which determines the usefulness of any drug. Such a balance varies according to the individual patient's needs. Thus a life-saving drug will be given even if it has serious side effects, while this would not be justifiable for a drug with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

1976
1976
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…In summary, although previous studies are not directly comparable either by virtue of the different patient groups studied, different neuroleptics used or differences in PET/tracer methodologies, and are potentially confounded by the effects of receptor upregulation, they all suggest that return to normal receptor availability (and neuroleptic washout) occurs between 24 and 156 h. The shorter "washout" times usually appear after relatively lower doses of neuroteptics. The present study finds that after single acute dosage in normal volunteers of 40 mg Ziprasidone, washout for the striatum, as indexed by a return to binding potential (BP) within the normal range (mean BP -2 SD), is seen at 18 h. This relatively rapid washout of neuroleptics from their striatal binding sites is at variance with clinical data which demonstrates pro-longed duration of action (Hershon et al 1972), but is in keeping with reported neuroleptic clearance rates from plasma and brain tissue (Forsman and Ohman 1977;Itoh et al 1984). The present study also adds to the evidence for a curvilinear relationship between neuroleptic concentrations and D 2 occupancy, in that at high blood concentrations of ziprasidone there is a relatively smaller decrease in binding potential (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…In summary, although previous studies are not directly comparable either by virtue of the different patient groups studied, different neuroleptics used or differences in PET/tracer methodologies, and are potentially confounded by the effects of receptor upregulation, they all suggest that return to normal receptor availability (and neuroleptic washout) occurs between 24 and 156 h. The shorter "washout" times usually appear after relatively lower doses of neuroteptics. The present study finds that after single acute dosage in normal volunteers of 40 mg Ziprasidone, washout for the striatum, as indexed by a return to binding potential (BP) within the normal range (mean BP -2 SD), is seen at 18 h. This relatively rapid washout of neuroleptics from their striatal binding sites is at variance with clinical data which demonstrates pro-longed duration of action (Hershon et al 1972), but is in keeping with reported neuroleptic clearance rates from plasma and brain tissue (Forsman and Ohman 1977;Itoh et al 1984). The present study also adds to the evidence for a curvilinear relationship between neuroleptic concentrations and D 2 occupancy, in that at high blood concentrations of ziprasidone there is a relatively smaller decrease in binding potential (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…The studies performed after neuroleptic with drawal showed return to l00% unoccupied sites within a few days (Figs 2 and 3), establishing that washout of neuroleptics from their striatal binding sites is a rapid process. Up till now, it was widely assumed that this washout was much slower, based on clinical, behavioural, and pharmacokinetic data (Hershon et a!, 1972;Marsden et a!, 1975;Byck, 1975;Korpi et a!, 1984;Campbell et a!, 1985). Our results, however, fully agree with reported neuroleptic clearance rates from plasma (Byck, 1975;Forsman & Obman, 1977;Itoheta/, 1984)andbraintissue (Ohman eta!, 1977), and with in vivo studies in rats (Saelens et a!, 1980; Ferrero et a!, 1983; Owen et a!, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In this report we point out prognostic factors for positive outcome. INeuropsychopharmacology 8:233-239, 1993J brand andFaurbye 1960;Paulson 1968;Crane 1973;Hershon et al 1972;Jeste et al 1979;Glazer et al 1984Glazer et al , 1990, whereas more recently and more frequently, new fIndings about remissions of TO symptomatology in pa tients receiving continuous NL treatment have been published (Casey 1985;1991;Casey et al 1986;Casey and Gardos 1990;Gardos et al 1988;Bergen et al 1989;Morgenstern et al 1987;Glazer et al 1991).…”
mentioning
confidence: 99%